SEMANTIC FEATURES OF THE ARABIC WORD ’ILM (BASED ON THE TREATISE IHSHA’ AL-’ULUM BY AL-FARABI) - Mustafayeva, A.A.; Issakhanova Kırca, M.M.; Paltore, Y.M. (Journal of Oriental Studies, 2025)
The treatise ‘Encyclopedia of Science’ or ‘Ihsha’ al-’Ulum’ by Abu Nasr al-Farabi is a comprehensive work that encompasses various science fields of that time, where the author was able not only to classify and systematize the sciences of his time but also to carry out an additional classification of each science with a definition of goals and objectives. The word ’ilm, is one of the most frequently used in the treatise and, perhaps, as the most recurrent, has not become the object of research to this day. Al-Farabi, a native of Farab and a non-native speaker of Arabic did not limit the meaning of the word to only ‘knowledge’, but also used it in the meaning of ‘science’. This article attempts to study the meanings of the word ’ilm with its cognate variants in the treatise of Abu Nasr al-Farabi’s ‘Encyclopedia of Science’ in the original Arabic text. Such research of a separate frequently used root in the original is being done for the first time in Farabi studies. The research aims to study the root ’ilm and its single-root models used by al-Farabi in the above-mentioned treatise. The research will also conduct a quantitative analysis of all single-root words from the root ‘’ilm’ to identify the frequency of their use. Keywords: Encyclopedia of Science’, ’ilm, science, knowledge, single-root words, al-Farabi, Arabic.